Personal financing planning: the importance of saving early for retirement plan / Nur Anati Khairudin - Khairudin, Nur Anati (2011)
Financial planning involves deciding what investments and activities would be most appropriate under both personal and broader economic circumstances. The purpose of this research is to identify the level of knowledge and employee’s awareness toward savings early for retirement. Therefore, from this research, it will help researcher to define and identifies the majority of population savings early for retirement. For the purpose of this study, the researcher has adopted the descriptive research design due to its used through survey method. The survey involved a structured questionnaire given to respondents and designed to elicit specific information. The population has been tested at Felcra Berhad Wilayah Tengah whereas its employees become the researcher’s respondent and 40 questionnaires were distributed among them. There are four types of analysis in SPSS program that had been used in the study to analyze the data frequency analysis, reliability testing, descriptive statistic and data correlations. From the findings, most of respondents agree that knowledge of financial planning is most important in creating awareness towards savings early for retirement. This study also finds out the most of respondents are disagree that savings some of income regularly is easy but most of respondent are agree that savings some of income regularly is important. Finally, the researcher can conclude that there is significant relationship for both of independent variables level of knowledge and employees’ awareness towards start savings early for retirement. Thus, researcher can make conclusion that both of independent variables have positive relationship with start saving early for retirement.